A dilemma of gas flaring and venting regulation in Colombia: Challenges of reconciling environmental protection and legal stability of investors (Encuentros, 2024)
The paper studies the problems brought about by Resolution 40066 of 2022 of the Ministry of Mines and Energy of Colombia, regarding the new requirements it sets up for the flaring and venting of natural gas in Colombia. These requirements, which must be followed by the investing companies, imply an investment in infrastructure and technology that may imply a contractual imbalance and a negative impact on foreign investors. From a documentary analysis method with a systematic and deductive approach, the authors analyze the problematic scenario posed by the resolution and concludes that it is necessary to find a balance between the two legal interests at stake: the environment and free enterprise. As a result, the paper supplies a comprehensive and integrative view of the State's obligation to protect the environment, but also to ensure a stable and predictable legal framework for investments.
Keywords: Regulação do gás natural; Estabilidade jurídica; Mudança climática; Contratos de estabilidade jurídica; Proteção ambiental